Forensic Accountants As Fraud Detectives: Lessons From The Indonesian Audit Board - A.Fadli Mappisabbi; Steviani Batti; Nurasia Natsir (International Journal of Economics, Management and Accounting, 2025)
Fraud poses a significant threat to organizational integrity and public trust, especially within governmental institutions. This study explores the critical role of forensic accountants in uncovering fraud within the Audit Board of the Republic of Indonesia. Using a case study approach, the research examines the application of advanced forensic data analytics by forensic accountants. It highlights the essential skills and characteristics that make forensic accountants effective, as well as their contributions to enhancing internal controls and governance mechanisms. The study demonstrates the impact of forensic accounting on fraud detection, prevention, and deterrence. The findings emphasize the importance of integrating forensic accounting expertise within the Audit Board's operational framework to strengthen its capacity to combat financial fraud. It also identifies challenges faced by forensic accountants, such as technological limitations and cultural resistance, and suggests strategies to overcome these barriers. By shedding light on the role of forensic accountants in safeguarding public sector integrity, this research contributes to the growing knowledge on forensic accounting practices in Indonesia. The insights can inform policies and capacity-building initiatives aimed at improving the Audit Board’s fraud detection capabilities, ultimately fostering greater public trust and accountability.